2015
DOI: 10.1002/phar.1572
|View full text |Cite|
|
Sign up to set email alerts
|

Successful Use of N‐Acetylcysteine to Treat Severe Hepatic Injury Caused by a Dietary Fitness Supplement

Abstract: In the absence of adequate premarketing efficacy and safety evaluations, adverse events from over-the-counter supplements are emerging as a public health concern. Specifically, bodybuilding products are being identified as a frequent cause of drug-induced liver injury. We present a case of a 20-year-old Hispanic male who presented with acute nausea and vomiting accompanied by severe right upper quadrant abdominal pain, shivering, and shortness of breath. Laboratory data pointed to mixed cholestatic and hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It has been used during several decades as mucolytic agent and also for the treatment of various disorders including paracetamol intoxication [228] . NAC has been also used for treatment of numerous disorders linked to oxidative stress including gastrointestinal [229] , renal [230] , cardiovascular [231] , pulmonary [232] , hepatic [233] , psychiatric and neurological disorders. The mucolytic activity of NAC is due to its ability to break up the disulfide bonds of the high molecular weight glycoproteins present in the mucus.…”
Section: Of Viral Infectionsmentioning
confidence: 99%
“…It has been used during several decades as mucolytic agent and also for the treatment of various disorders including paracetamol intoxication [228] . NAC has been also used for treatment of numerous disorders linked to oxidative stress including gastrointestinal [229] , renal [230] , cardiovascular [231] , pulmonary [232] , hepatic [233] , psychiatric and neurological disorders. The mucolytic activity of NAC is due to its ability to break up the disulfide bonds of the high molecular weight glycoproteins present in the mucus.…”
Section: Of Viral Infectionsmentioning
confidence: 99%
“…It is well established that NAC has been proven to decrease the burden of acetaminophen toxicity on the liver by replenishing glutathione which converts toxic metabolites (NAPQI) into benign products . It also has the ability to scavenge oxygen‐derived free radicals and improve endothelium‐dependant perfusion to the liver . Like acetaminophen, cocaine also has toxic metabolites (norcocaine and N‐hydroxynorcocaine) that cause liver damage .…”
Section: Discussionmentioning
confidence: 99%
“…NAC's role has not been well established as an antidote for nonacetaminophen drug‐induced (NADI) liver failure. A prospective trial showed significantly improved transplant‐free survival at 3 weeks and at 1 year (52% vs. 30%) with the use of NAC for the treatment of NADI liver failure . Another trial showed that NAC was associated with a statistically significant survival benefit (47% vs. 27%) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations